Teaching by principles : - Brown, H. Douglas (Longman, 2001)
Teaching by Principles: An Interactive Approach to Language Pedagogy, Third Edition, by H. Douglas Brown, is a widely acclaimed methodology text used in teacher education programs around the world. This user-friendly textbook offers a comprehensive survey of practical language teaching options, all firmly anchored in accepted principles of language learning and teaching. End-of-chapter exercises give readers opportunities to process material interactively. Suggested readings direct readers to important books and articles in the field.